Microbial testing in food safety management (New York, 2002)
Describes the role of microbiological testing in modern food safety management systems. This title explores how risk assessment and risk management can be used to establish goals for use in controlling food borne illness. It provides guidelines for establishing effective management systems to control specific hazards in foods.
Keywords: Food,Thực phẩm; Microbiology,Vi sinh vật